Towards professionalization of school leadership - Miovska Spaseva, Suzana (Vodenje v vzgoji in izobraževanju, 2014)
The article examines the issue of school leadership development as one of the key priorities of the educational policy agendas throughout the world. The main attention is given to the global trends defined by the oecd for professionalization of school leadership: (Re)defining school leadership responsibilities, Distributing school leadership, Developing skills for effective school leadership, Making school leadership an attractive profession. Within this general framework of expectations the current situation of school leadership in Macedonia is presented. The analysis is focused on the compatibility of the theory and practice of educational leadership in Macedonia, the challenges of the sustainability of the planned and implemented activities and the further possibilities for developing the school leadership in the country.
Keywords: education; leadership; Macedonia; Makedonija; profesionalizacija; profesionalni razvoj; professionalization; ravnatelji; Republic of Macedonia; school leadership; strokovna usposobljenost; vodenje